DNA barcoding of rhopalosomatid larvae reveals a new host record and genetic evidence of a second species of Rhopalosoma Cresson (Hymenoptera, Rhopalosomatidae) in America north of Mexico - Lance A. Miller; Torie D. Benefield; Sarah A. Lounsbury; Volker Lohrmann; Jeremy D. Blaschke (Journal of Hymenoptera Research, 2019)
Rhopalosomatidae are unusual wasps whose larvae develop as ectoparasitoids on crickets. In America north of Mexico, three genera and six species are recognized. Host species are known only for Rhopalosoma nearcticum Brues and include Hapithus agitator Uhler, H. brevipennis (Saussure), and H. saltator (Uhler) (Gryllidae: Hapithinae). Here we report a new host species: the Anaxipha exigua (Say) species-group (Trigonidiidae: Trigonidiinae) discovered by barcoding nine rhopalosomatid larvae collected from Cypress Grove Nature Park, Jackson, Tennessee. Rhopalosoma nearcticum is currently the only documented species of Rhopalosoma Cresson in America north of Mexico, but our phylogenetic analyses recovered two genetically distinct clades of Rhopalosoma and thus reveal the presence of at least two species of Rhopalosoma in America north of Mexico.